Analisis Kemampuan Beripikir Kreatif Matematis Siswa SMP - Siti Elva Hepzibah; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
Mathematical learning is given at each stage, taught so that students can use mathematics as a way of reasoning. The reality in the field of education in schools is more about students' intelligence for the development of student creativity. Meanwhile, it is equally important to achieve student success in learning. Students are asked to process information about processing information. Here the teacher gives freedom to students in expressing opinions in the learning process. This freedom can be realized with students who are given the freedom to solve mathematical problems in various ways. In learning mathematics at a private junior high school in Bandung, specifically on the subject of straight line and gradient equations, students find it difficult to understand the meaning of straight line and gradient stories, difficulties in understanding methods and still confused which method to use to answer questions question given by the teacher. So the classroom action research (CAR) was held to improve students' mathematical thinking skills using open consent, this study was conducted with 2 cycles and 8 meetings. The results of this study indicate that students can improve the quality of the test results tested in each test. In addition, the average value of the initial test results of 17.5 then increased to 64.75 on the results of the first cycle test, then increased again to 74.72222 on the results of the cycle II test. This shows an increase in the ability of Grade VIII students at Mutiara 4 Bandung Middle School can be improved through open agreement.